FAKTOR DOMINAN YANG MEMENGARUHI MOTIVASI KERJA, KINERJA, DAN KEPUASAN KERJA GURU SMA - Madyo Ekosusilo; Soepardjo Soepardjo (Universitas Negeri Malang, 2015)
Abstract: The Dominant Factors Affecting Motivation, Performance, and Job Satisfaction of High School Teachers. This study is aimed at identifying the effects of organizational culture, headmaster's leadership behaviors, and pedagogical competence on teachers' work motivation, performance and job satisfaction. Research samples included 107 teachers in Karanganyar Regency. Data were collected through questionnaires and analyzed using path analysis by employing a computer software, SPSS 17.00. The results indicated that there were positive and significant effects of organizational culture, headmaster's leadership behaviors, and pedagogical competence on teachers' work motivation, performance and job satisfaction, either directly or indirectly. The organizational culture had the dominant effect on teachers' job satisfaction, followed by performance, work motivation, pedagogical competence, and headmaster's leadership behaviors. Keywords: organizational culture, leadership behaviors, pedagogical competence, work motivation, performance, job satisfaction Abstrak: Faktor Dominan yang Memengaruhi Motivasi Kerja, Kinerja, dan Kepuasan Kerja Guru SMA. Penelitian ini bertujuan untuk mendeskripsikan pengaruh budaya organisasi, perilaku kepemimpinan kepala sekolah, dan kompetensi pedagogik terhadap motivasi kerja, kinerja, dan kepuasan kerja guru. Sampel berjumlah 107 guru di Kabupaten Karanganyar. Pengumpulan data dilakukan dengan angket, dan analisis data menggunakan analisis jalur dengan bantuan komputer program SPSS 17.00. Hasil penelitian membuktikan bahwa ada pengaruh yang positif dan signifikan budaya organisasi, perilaku kepemimpinan kepala sekolah, dan kompetensi pedagogik terhadap motivasi kerja, kinerja, dan kepuasan kerja guru baik secara langsung maupun tidak langsung. Budaya organisasi paling besar pengaruhnya terhadap kepuasan kerja guru, disusul kinerja, motivasi kerja, kompetensi pedagogik, dan perilaku kepemimpinan kepala sekolah. Kata kunci: budaya organisasi, perilaku kepemimpinan, kompetensi pedagogik, motivasi kerja, kinerja, kepuasan kerja